Exploring the transformation of news writing style in digital news portals - Mior Kamarulbaid, Afiqah (2021)
Journalism's core ingredient is the news writing style, which is one of the most crucial parts of the media industry since it determines whether something is considered noteworthy or otherwise. Due to the rising of Internet penetration, which have led to the rise of digital media, in particular social media, the journalism profession's of environment has shifted drastically and continues to confront new problems and possibilities as it advances toward technological modernity. This study's aims were achieved using a qualitative phenomenological approach, where ten media professionals were interviewed up to the data saturation point. Accordingly, an interview guide aided the interview procedure which was captured using digital voice recorders. The data were transcribed verbatim and organised into groups to generate codes, categories, and themes. According to the study's findings, the journalists have employed four unique news writing styles when informing their audience of the news stories. Numerous variables, including the characteristics of digital media, demographic trends, industry segmentation, and the demand for speed, have affected the growth of the news writing style in digital news portals. These changes in news writing style and circumstances have driven alterations in writing practices, which impacted content, the journalists, and media organisations. Additionally, the study's findings show how news writing styles have evolved in digital news portals. It is essential for media workers, educators, and journalism students to understand how the news writing style has evolved in digital news portals. It will be possible to negotiate an agreement with the news site based on the results that would allow the media sector to create specific criteria to address concerns about harm and transparency in the news. This study contributes to the body of knowledge by illustrating how the transformation of news writing styles in digital portals has given new journalistic practises significance.